Fear and Architecture: Learning from Mega-Projects and Canal Istanbul as a Case - Ece Ceylan Baba; Cansu Aktaş; Ceren Balioğlu; Taylan Kaba (Journal of Contemporary Urban Affairs, 2023)
Fear has been a fundamental aspect of human existence throughout history, and its connection with architecture has evolved as cities and the built environment have changed. Mega-projects, such as Canal Istanbul, play a significant role in shaping urban fear. Considering this fact, this study explores the relationship between fear and architecture in the context of mega-projects, with a focus on the case of Canal Istanbul, to define fear, identify its different types (environmental, socio-economic, technological), and examine their common underlying factor: generating a situation of uncertainty. The research investigates the Canal Istanbul project as a case study, presenting arguments supported by theoretical sources to explore the relationship between fear, architecture, and uncertainty. In this regard, this study adopts a qualitative and interpretive research approach. It provides insights into the potential consequences of the Canal Istanbul project concerning fear and architecture by emphasizing the importance of transparency and public participation in mega-projects, highlighting the need for detailed analysis and scientific references. Overall, the research contributes to understanding the interplay between fear, architecture, and mega-projects, offering valuable insights for future urban planning and development.